Efficacy and predictors of response to somatostatin analogues in patients with ectopic ACTH syndrome - Olga O. Golounina; Zhanna E. Belaya; Alla A. Markovich; Liudmila Y. Rozhinskaya; Galina A. Mel`nichenko; Natalia G. Mokrysheva; Ivan I. Dedov (Терапевтический архив)
Aim. To study the immediate efficacy, tolerability and predictors of response to prolonged-acting somatostatin analogues (SSAs) in patients with ectopic ACTH syndrome (EAS).